1982
DOI: 10.3133/ofr82823
|View full text |Cite
|
Sign up to set email alerts
|

Illustrations of gravity models of the southeast limb of the Blacktail-Snowcrest uplift, southwest Montana

Abstract: Also included is a map showing the location of gravity stations used in the models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…38) can be explained by postulating the presence of older structures in the foreland that were truncated by the west-to-east directed thrust faults of the Cordilleran fold-thrust belt. Though Dahlstrom (1970, p. 382) Recent geological and geophysical studies (Perry and others, 1981;Perry and others, 1983;Kulik and Perry, 1982) have indicated the presence of a major subsurface east-northeast-trending, lowangle thrust fault zone northeast of this study area, the sub-Snowcrest thrust, that juxtaposes Archean basement crystalline rocks from the northwest over thick Cretaceous sedimentary rocks on the southeast. Aligned gravity highs identified by Kulik (in Skipp, Lucchitta, and Kulik, 1983), that characterize the sub-Snowcrest fault zone, extend southwestward into the study area ( Fig.…”
Section: Several Large Normal Faults Between Railroad Canyon and Petementioning
confidence: 74%
“…38) can be explained by postulating the presence of older structures in the foreland that were truncated by the west-to-east directed thrust faults of the Cordilleran fold-thrust belt. Though Dahlstrom (1970, p. 382) Recent geological and geophysical studies (Perry and others, 1981;Perry and others, 1983;Kulik and Perry, 1982) have indicated the presence of a major subsurface east-northeast-trending, lowangle thrust fault zone northeast of this study area, the sub-Snowcrest thrust, that juxtaposes Archean basement crystalline rocks from the northwest over thick Cretaceous sedimentary rocks on the southeast. Aligned gravity highs identified by Kulik (in Skipp, Lucchitta, and Kulik, 1983), that characterize the sub-Snowcrest fault zone, extend southwestward into the study area ( Fig.…”
Section: Several Large Normal Faults Between Railroad Canyon and Petementioning
confidence: 74%
“…The Sage Creek normal fault forms the southeastern margin of this basin. Gravity modeling (Kulik, 1982;Kulik and Perry, this volume) suggests that this Tertiary fault is listric and merges at depth with the subSnowcrest thrust, dipping somewhat more steeply northwest than the latter, as indicated by Perry and others (1983a, Fig . 12).…”
Section: Sage Creek Normal Fault the Sagementioning
confidence: 85%
“…6, 8B), much more deformed and overturned than those to the north, suggests proximity to a major subsurface thrust, the subjacent sub-Snowcrest thrust of previous reports by and others (1981,1983a). This is inferred from gravity data and gravity modeling to be a major northwest-dipping buried foreland thrust beneath the Snowcrest structural terrane, on which the deformed Paleozoic and lower Mesozoic rocks of the Snowcrest terrane-the hanging wall-moved southeastward over Cretaceous footwall rocks (Kulik, 1982;Kulik and Perry, 1982 and this volume;Kulik, 1982,1983). Subsurface geological data are insufficient to draw well-constrained cross sections across the Snowcrest structural terrane or SnowcrestGreenhorn thrust system.…”
Section: Cretaceous Rocksmentioning
confidence: 97%
“…1). Distribution of geologic map units, differences in thicknesses of upper Paleozoic rock units, ages and stratigraphic relations of Cretaceous synorogenic deposits, the alignment of gravity highs, and the distribution of aeromagnetic contours indicate that the foreland in southwestern Montana was faulted before the Cordilleran thrusts moved across it (Kulik and Perry, 1982;Kulik and others, 1983;Perry and others, 1981;Perry and others, 1983;Ryder and Scholten, 1973;Nichols and others, 1985;. Positions of these foreland faults appear to have had a Precambrian ancestry (Schmidt and O'Neill, 1983;Schmidt and Garihan, 1983).…”
Section: B Skippmentioning
confidence: 96%